1993
DOI: 10.1093/geronj/48.1.m6
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Blood Flow Response to Constant Pressure in Healthy Older and Younger Subjects

Abstract: This study compared the dermal blood flow response to low levels of compressive pressure in healthy older and younger subjects. Dermal blood flow was measured over the left trochanter of 19 younger (21-45 yrs) and 22 older (> or = 60 yrs) subjects using a laser-Doppler velocitometer. Interface pressure, baseline flow, and flow during 60 minutes of left-side lying on an air mattress were measured. Baseline dermal blood flow did not differ significantly between the older and younger groups. Both groups showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 0 publications
1
13
1
Order By: Relevance
“…Sanada et al showed that the patients who developed pressure ulcers after long surgeries were the same ones who had no increase in blood flow during the surgery (Sanada et al, 1997). Xakellis et al showed that healthy subjects of different ages lying on a mattress and exposed to pressures less than 32 mmHg demonstrated a significant increase in dermal blood flow (Xakellis et al, 1993). They speculated that the origin of this "unexpected increase" was a vasodilatory reflex in response to the vessels being partially occluded.…”
Section: Perspectives On Microcirculation and Pressure Ulcer Etiologymentioning
confidence: 99%
“…Sanada et al showed that the patients who developed pressure ulcers after long surgeries were the same ones who had no increase in blood flow during the surgery (Sanada et al, 1997). Xakellis et al showed that healthy subjects of different ages lying on a mattress and exposed to pressures less than 32 mmHg demonstrated a significant increase in dermal blood flow (Xakellis et al, 1993). They speculated that the origin of this "unexpected increase" was a vasodilatory reflex in response to the vessels being partially occluded.…”
Section: Perspectives On Microcirculation and Pressure Ulcer Etiologymentioning
confidence: 99%
“…There is no simple relationship between interface pressure and skin blood flow perfusion or oxygen tension (FELDMAN et al, 1993;XAKELLIS et al, 1993). Therefore interface pressure measurements alone are not sufficient as a sign of tissue status (BRIENZA and GEYER, 2000;MAYROVlTZ and SIMS, 2002;WHITTEMORE, 1998).…”
Section: Pressure Sore Aetiologymentioning
confidence: 99%
“…In healthy individuals, irrespective of their age, the dermal blood flow increases when low levels of external pressure axe applied (FRANTZ and XAKELLIS, 1989;HERRMAN et al, 1999;PATEL et al, 1999;XAKELLIS et al, 1993), whereas the response pattern for elderly patients at risk of pressure sores is inconsistent . Upon relief of pressure, debilitated individuals demonstrate an impaired and delayed tissue recovery compared with healthy individuals (BADER, 1990).…”
Section: Pressure Sore Aetiologymentioning
confidence: 99%
“…The cutaneous resistance vessels function in autoregulation of blood flow and reactive hyperemia. 24 Xakellis et al (1993) hypothesized that the normal hyperemic response to external pressure is the result of a compensatory vasodilatation of dermal circulation that serves to minimize the damage from the compressive pressure. 25 Reduced hyperemic response may result from capillary damage, endothelial dysfunction, capillaries being plugged by leukocytes, or failure of the capillaries to dilate.…”
Section: Reactive Hyperemiamentioning
confidence: 99%
“…Higher external pressure produces a longer hyperemic response time. Some researchers further suggest that pressure ulcer development may be related to a lack of physiologic increase 25,26 in blood flow after pressure is relieved.…”
Section: Changes In the Hyperemic Responsementioning
confidence: 99%